Studies on Genetic Variability, Heritability, Genetic Advance, Correlation Coefficient and D2 Analysis in Sweet Potato (Ipomoea batatas L.) - Bhadauriya, Pankaj Singh; Deo, Chandra; Ram, C. N.; Verma, S. K.; Singh, Sudheer (Indian Journal of Hill Farming, 2018)
Thirty six diverse genotype of sweet potato collected from different location of India were evaluated for nineteen quantitative and qualitative characters in Randomized Block Design with three replications at Main Experiment Station, Department of Vegetable Science, NDUAT, Kumarganj, Faizabad(UP) during October, 2011 to March, 2012. On the basis of mean data, the existence of very high degree of variability was observed in the germplasm. The genotypes, NDSP-65 (375g) followed by SP-594 (354g), 187017 (336), NDSP-1-4 (333) and NDSP-1-3 (324g) were the best yield performer for tuber yield per plant. High genotypic coefficient of variability and phenotypic coefficient variability were estimated for number of branches per vine followed by internodal length, length of vine, number of leaf per vine, girth of tuber and acidity. High heritability coupled with high genetic advance in percent of mean were recorded for number of branches per vine, internodal length, length of vine, number of leaf per vine, acidity, average weight of tuber, number of tubers per vine, TSS and width of leaf. Tuber yield (q/ha) followed by tuber weight, internodal length, specific gravity and tuber length showed positive significant correlation with tuber yield per plant while, TSS and moisture per cent showed negative significant correlation with tuber yield per plant. Path coefficient analysis revealed that, tuber weight followed by tuber per vine, tuber yield (q/ha) showed higher value of positive direct effect on tuber yield per plant while, tuber yield followed by specific gravity via tuber weight and branches per vine, length of vine and laves per vine via tuber per vine, vine length and leaves per vine showed positive indirect effect on tuber yield per plant. Total of 36 genotype were grouped in to seven cluster. The highest intra cluster distance was found in cluster V and inter cluster distance between cluster IV and VI. Internodal length (31.59%) number of branches per vine (21.90%) and acidity (21.11%) were found as the important traits in clustering the genotype with different groups. Based on above finding it might be concluded that these are existing sufficient variability in the available germplasm. Genotype (NDSP-65 followed by SP-594, 187017, NDSP-1-4 and NDSP-1-3) may be exploited in future after further evaluation for stability test.